[Kalendarz podziemny na rok 1986 wydany przez Solidarność Zielona Góra] . Unofficial calendar for 1986 by Solidarity from Zielona Góra - Solidarność Zielona Góra. (Solidarność Zielona Góra, 1986)
B&w photo reproduction of a calendar. The calendar contains several graphic images: Solidarity logotype with a flag, the crest of the city of Zielona Góra, a symbol merging cross with anchor, portrait of rev. Jerzy Popiełuszko and his obituary plaque.